2023
DOI: 10.1101/2023.02.13.527877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent patterns of meiotic double strand breaks and synapsis initiation dynamics suggest an evolutionary shift in the meiosis program between American and Australian marsupials

Abstract: In eutherian mammals, hundreds of programmed DNA double-strand breaks (DSBs) are generated at the onset of meiosis. The DNA damage response is then triggered. Although the dynamics of this response is well studied in eutherian mammals, recent findings have revealed different patterns of DNA damage signaling and repair in marsupial mammals. To better characterize these differences, here we analyzed synapsis and the chromosomal distribution of meiotic DSBs markers in three different marsupial species (Thylamys e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…Moreover, a recent study has shown that the bouquet configuration is required for the distal bias of DSB formation and repair, possibly playing an important role in the observed reduced recombination rates at interstitial positions 73 . Future experiments in Rhynchospora will be important to identify conserved and adapted mechanisms about the role of spatiotemporal dynamics of meiotic DSB formation and HEI10 loading in shaping the recombination landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study has shown that the bouquet configuration is required for the distal bias of DSB formation and repair, possibly playing an important role in the observed reduced recombination rates at interstitial positions 73 . Future experiments in Rhynchospora will be important to identify conserved and adapted mechanisms about the role of spatiotemporal dynamics of meiotic DSB formation and HEI10 loading in shaping the recombination landscape.…”
Section: Discussionmentioning
confidence: 99%